The diagnostic value of hyperammonaemia induced by the non-ischaemic forearm exercise test. Issue 10 (11th April 2017) - Hogrel, Jean-Yves; Janssen, Jorien B E; Ledoux, Isabelle; Ollivier, Gwenn; Béhin, Anthony; Stojkovic, Tanya; Eymard, Bruno; Voermans, Nicol C; Laforet, Pascal
Abstract : Aims: The non-ischaemic forearm exercise test (NIFET) is used as a diagnostic tool for the screening of patients with exercise intolerance and for the diagnosis of various metabolic muscle disorders. The production of lactate and ammonia are generally analysed to guide the diagnosis. The aim of this retrospective study was to determine the level of ammonia rise, which can be suggestive of a muscle disease. Methods: This retrospective study involved 1440 patients who underwent NIFET. The clinical files of the patients with hyperammonaemia were methodically studied. Normal values were derived from 60 healthy controls. Results: 110 patients with hyperammonaemia were detected. They were classified as either having mild (between 94 and 141 µmol/L) or severe (more than 141 µmol/L) hyperammonaemia. Their diagnosis was studied with respect to the increase in lactate induced by the NIFET. Conclusions: Severe postexercise hyperammonaemia, even in the presence of a normal lactate response, is strongly suggestive of a muscle glycogen storage disease. Mild hyperammonaemia in the absence of other abnormalities is most likely non-specific and not indicative of a muscle disease.